The Relationship of Workload, Knowledge, and Supervision with Nurse Adherence to Infection Prevention Protocols - Muhamad Nor Mudhofar (Professional Evidence-based Research and Advances in Wellness and Treatment, 2024)
Nurse adherence to infection prevention protocols is crucial for reducing Healthcare-Associated Infections (HAIs). Yet, compliance remains suboptimal in many facilities due to high workload, varying knowledge levels, and inconsistent supervision. Purpose: This study analyzes the relationship between workload, knowledge, supervision, and nurse compliance with infection prevention protocols at RSUD dr. Rasyidin Padang. Methods: A quantitative correlational design was employed with 65 nurses selected via total sampling. Questionnaires assessed workload, knowledge, supervision, and compliance. Data were analyzed using Pearson correlation. Results: Workload showed a significant negative correlation with compliance ( ;  ). Knowledge ( ;  ) and supervision ( ;  ) had significant positive correlations. Supervision emerged as the strongest factor. Implications: Findings highlight the need for balanced workloads, ongoing training to boost knowledge, and structured supervision to enhance protocol adherence. Conclusion: Workload, knowledge, and supervision significantly influence nurse compliance. Sustainable interventions targeting these factors are essential for improving service quality.